Capacity Building in Economics Education and Research - Bourguignon, François (Washington, DC: World Bank, 2012)
This paper is a contribution to our understanding of building local capacity in economics education and research in developing and transition countries. The contributors and discussants in this publication provide many insights on these issues. In particular, they offer a deep reflection on the need for capacity building in economics education and research in each region. For the last 15 years, The World Bank, its partners, and government have supported the "centers of excellence" for building capacity in modern economics education and research in developing and transition countries. To strengthen these efforts, the Central European University (CEU) and the World Bank jointly organized a conference entitled "Scaling Up Capacity Building in Economics Education and Research: Lessons Learned and Future Directions," which took place at the CEU campus in Budapest, Hungary, on June 14-15, 2005. The material from this conference is covered in this publication.